Brain Drain di Indonesia - June Cahyaningtyas (Jurnal Paradigma, 2011)
This research analyses the issue of brain drain in Indonesia. The analysis is focused upon the inquiries on the motives behind the decision made by skilled labors to work abroad. With the focus being taken, the research tried to look whether there is or there is no correlation between the conception of brain drain with the rationale that lies behind the decision to work outside. Thus, this research aimed at confirming the context of the hypothetical arguments through the first hand experience. Moreover, this research wanted to find out the mechanism through which the skilled labor migration has continually been preceding from Indonesia.                  To go over this purpose, this research used the interpretation method from the online ethnography research techniques, via the unstructured interview (directly or indirectly) with informants, also observation on the discourse developed within the internet-based community network of academicians and researches that seek to find opportunities of earning education, doing researches, or vacancy abroad in beasiswa mailing list. The informants of the research are those who have been living or are planning to go abroad as skilled labors.